The Effects of Seasons, Age of the Animal and Storage Time on Physical Properties of Camel’s Meat (Camelus Dromedarius - Arabi, Omer H.; Elmawlla, Selam Fadl; Abdelhai, Elsir; Elhadi, Abdulmunem (Gezira Journal of Engineering and Applied Sciences, 2018)
The aim of this study was to determine the effect of age of the animal and storage time on the physical properties of camel’s meat in autumn, summer and winter seasons. A total number of 135 meat samples from camels ranged between 1-9 years age were chosen. The samples were analysed for pH, water holding capacity, oxidative rancidity and color determination. The ultimate pH and water holding capacity showed a significant difference (p >0.05) in different seasons and storage periods. The rancidity and color determination of meat showed significant difference (p >0.05) in different seasons, different storage period and different age of the animals. The study concluded: those different seasons had a significant effect on the quality of camel’s meat, due to its effect on pH and water holding capacity. Age of the animals had a significant effect on water holding capacity, rancidity and colour, but it had no significant effect on pH. The storage period had a significant effect on the oxidative rancidity and colour that affect the shelf life of meat.